Investigation of the Effects of Recreational Football on Some Functional Movement Skills in Older Men - Alparslan Ünveren; Cemal Polat (Türk Spor ve Egzersiz Dergisi, 2023)
This study aimed to examine the effects of recreational football on functional movement skill (FMST) levels of elderly men. 57 (65.05 ± 2.5) elderly men who participated in the study were randomly divided into the football group (FG, n= 28) and the control group (CG, n= 29). Data were collected with the FHTT scale and investigeted via mixed design ANOVA. The data were analyzed considering the significance level of p<.05. There was no statistically significant difference between the groups in the deep squatting movement (p>.096), and there was a statistical difference between the times (p<.002). Statistically significant differences were observed between groups, between times and group*time interaction at high stepping, respectively (p<.008, p<.001, p<.035). Statistically significant differences were observed between groups in a single-line move and in group*time interaction, respectively (p<.008, p<.006). There was a statistically significant difference between the groups in shoulder mobility (p<.001). There was no statistically significant difference between the times and in the group*time interaction, respectively (p>.98, p>.44). Statistically significant differences were observed between groups, between times and in group*time interaction in active straight leg raising, respectively (p<.004, p<.001, p<.035). There was no statistically significant difference between the groups in trunk stability movement (p>.089). There was a statistically significant difference between the times and in the group*time interaction (p<.024). Statistically significant difference was observed between groups and between times in rotational stability movement, respectively (p<.001, p<.001). There was no statistically significant difference in the groups*time interaction (p>.065). Statistically significant differences were observed in FHTT total scores between groups, between times and in the interaction of groups*time, respectively (p<.001, p<.001, p<.001, p<.001). The results show that recreational football is effective on FHTT and is a powerful exercise option in improving mobility, which is important for elderly individuals to maintain their quality of life.